Bright, relatively isolated star clusters in PHANGS-HST galaxies: aperture corrections, quantitative morphologies, and comparison with synthetic stellar population models - Deger, Sinan; Lee, Janice C; Whitmore, Bradley C; Thilker, David A; Boquien, Mederic; Chandar, Rupali; Dale, Daniel A; Ubeda, Leonardo; White, Rick; Grasha, Kathryn; Glover, Simon; Schruba, Andreas; et al. (Monthly notices of the Royal Astronomical Society, 2022)
Using PHANGS-HST NUV-U-B-V-I imaging of 17 nearby spiral galaxies, we study samples of star clusters and stellar associations, visually selected to be bright and relatively isolated, for three purposes: to compute aperture corrections for star cluster photometry, to explore the utility of quantitative morphologies in the analysis of clusters and associations, and to compare to synthetic stellar population models. We provide a technical summary of our procedures to determine aperture corrections, a standard step in the production of star cluster candidate catalogues, and compare to prior work. We also use this specialized sample to launch an analysis into the measurement of star cluster light profiles. We focus on one measure, M20 (normalized second-order moment of the brightest 20 per cent of pixels), applied previously to study the morphologies of galaxies. We find that M20 in combination with UB-VI colours, yields a parameter space where distinct loci are formed by single-peaked symmetric clusters, single-peaked asymmetric clusters, and multipeaked associations. We discuss the potential applications for using M20 to gain insight into the formation and evolution of clusters and associations. Finally, we compare the colour distributions of this sample with various synthetic stellar population models. One finding is that the standard procedure of using a single-metallicity SSP track to fit the entire population of clusters in a given galaxy should be revisited, as the oldest globular clusters will be more metal-poor compared to clusters formed recently.
Advance access publication 2021 November 12
Gesehen am 20.04.2022